Evaluation of Seroprevalence of HBsAg and Anti-HCV in the Patients Admitted to the Tunceli State Hospital - Asan, Ali; Akbulut, Ayhan; Sacar, Suzan; Turgut, Huseyin (Galenos Yayincilik, 2011)
Viral hepatitis cases constitute the leading group of liver diseases both in our country and worldwide. The aim of the current study was to investigate seropositivity of HbsAg and anti-HCV in the patients who were admitted to the outpatient clinics of Tunceli State Hospital between January 2010 and December 2010. All HBsAg and anti-HCV levels were determined by chemiluminescence immunoassay method (Architect i2000, Abbott, USA) and the results were evaluated retrospectively. Statistical analysis of the results was performed using Fisher's Chi-square test. The seroprevalence of HBsAg was 4.22% and anti-HCV was 0.95%. The seroprevalences of HBsAg and anti-HCV among females were 3.50% and 0.92%, respectively, whereas 4.99% and 0.98% among males, respectively. The seroprevalences of HBsAg and anti-HCV were higher in males than females (p>0.05). When the seroprevalences were evaluated according to the age groups, HBsAg seropositivity was most frequently observed in 50-59 years of age group both in males and females; whereas, anti-HCV seropositivity was most frequent in the >= 70 years of age group. In the present study, HBsAg positivity was detected in two cases; a one year old and a six year old child born following the initiation of national immunization program. In conclusion; seropositivities of HBsAg and anti-HCV were determined to be similar to the mean levels in the eastern-southeastern regions, though they were higher than those in Turkey. Since no previous similar studies have been conducted in Tunceli province, it was not possible to perform a comparison or an overall evaluation for the city. The scope of the immunization program, which has been currently conducting by Ministry of Health, should be extended to include risk groups and necessary preventive measures should be taken as well
Keywords: HBsAg; anti-HCV; seroprevalence